PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERBANDINGAN TRIGONOMETRI KELAS X MIPA-1 SMA NEGERI 1 BAMBALAMOTU: Application Of The Contextual Teaching And Learning (Ctl) Approach To Improve Students' Learning Outcomes In The Material Of Trigonometric Ratios Of Class X Mipa-1 Sma Negeri 1 Bambalamotu - Asis, Nurasia; Idris, Mustamin; Murdiana, I Nyoman (Universitas Tadulako, 2024)
The purpose of this study was to obtain a description of the application of the Contextual Teaching and Learning (CTL) approach to improve student learning outcomes in trigonometry comparison materials in class X MIPA-1 SMA 1 Bambalamotu. The type of research used in this study was Classroom Action Research (CAR) developed by Kemmis and Mc. Taggart which carried out consists of 3 stages, namely (1) Planning, (2) the Implementation of actions and observations and (3) reflection. This research was conducted in two cycles. The subjects of this study were all students of class X MIPA-1 as many as 30 students and 3 students were selected as informants with high, medium, and low abilities. The results sgowed that the application of the Contextual Teaching and Learning (CTL) approach could improve student learning outcomes in the Triginimetry Comparison Material of Class X MIPA-1 SMA Negeri 1 Bambalamotu by following the CTL components contained in the learning activities as follows : 1) Contructivism; 2) Inquiry; 3) Learning Comonity; 4) Question; 5) Modeling; 6) Reflection; and 7) Authentic assessment. The results of observation of teacher and student activities also experienced an increase where in cycle I there were still those who got less scores, but in cycle II all aspects that were assessed were getting good and very good ratings. The results of the final action test obtained by the students experienced completeness as many as 13 people and increased in the second cycle, it was obtained that 25 students experienced comletenness.